ChemInform Abstract: 2‐(Pyridinium‐1‐yl)‐1, 1‐bis(triflyl)ethanides: Structural Behavior and Availability as Bis(triflyl)ethylating Reagents. Issue 8 (25th February 2014) - Yanai, Hikaru; Takahashi, Yoichi; Fukaya, Haruhiko; Dobashi, Yasuo; Matsumoto, Takashi
Abstract The synthesis of stable, non‐hygroscopic, and easy‐to‐handle zwitterionic title structures from heterocyclic arenes is presented.